Modelling coral calcification rates in Orbicella faveolata (Cnidaria: Scleractinia) using light attenuation coefficients in water (KdPAR) - Gutiérrez-Estrada, Gabriela; Tortolero-Langarica, J.J. Adolfo; Carricart-Ganivet, Juan P. (Marine environmental research, 2025)
Coral calcification represents a vital process within coral reef ecosystems, wherein reef-building corals contribute significantly to the physical construction and maintenance of the reef framework. The calcification process is related to the photosynthesis of endosymbiotic algae, where light plays a crucial role in coral energetic tradeoffs. However, local stressors have led to increased turbidity, subsequently affecting light availability, especially in nearshore reefs. This study proposes a light-driven model designed to predict coral calcification in Orbicella faveolata under different light conditions, using the diffuse attenuation coefficient in water (KdPAR) as a predictive parameter. To determine annual calcification across different light conditions, we collected coral skeleton samples across depth gradients (∼5–38 m) at five reef sites in the Mexican Caribbean. Sclerochronological characteristics were analyzed through X-ray imaging and KdPAR values were obtained using in-situ light measurements. The results indicate that as light PAR is attenuated with depth, coral skeletal density increases and extension rate decreases. Likewise, annual calcification also responds to the underwater light field. However, calcification shows a pattern that can be explained by a nonlinear Gaussian function and shows that 60 % of surface PAR is needed for optimal calcification. This function was used to predict annual calcification in different suboptimal KdPAR conditions. This report presents the first model of annual calcification of O. faveolata using KdPAR. The results provide significant ecological insights into coral calcification and underscore the importance of conserving optimal optical properties of the water column to sustain coral growth and provides a better understanding of coral distribution and their contribution to reef framework development across vertical gradients in the Caribbean region. •Orbicella faveolata, a keystone reef-building coral, exhibits a vertical distribution influenced by light availability.•Reduced light penetration in reef environments can significantly compromise the calcification process of O. faveolata.•Calcification model based KdPAR is a valuable tool for predicting the amount of CaCO3 contributed by O. faveolata.•The KdPAR holds significant potential as an indicator for estimating calcification rates in O. faveolata.